The price of looking sexy: visual ecology of a three‐level predator–prey system. (13th October 2016) - Outomuro, David; Söderquist, Linus; Johansson, Frank; Ödeen, Anders; Nordström, Karin
Summary: Colour signals and colour vision play a pivotal role in intraspecific communication and predator–prey interactions. However, the costs of expressing conspicuous sexual signals at multiple trophic levels have been largely overlooked. Sexual signals can also experience character displacement in sympatric populations of closely related species, leading to potential changes in conspicuousness. We here investigate a bird–damselfly–fruit fly predator–prey system, where two closely related damselfly species have conspicuous, sexually selected wing coloration. The damselflies can occur in sympatry and allopatry, and reproductive character displacement in the coloration size has been previously reported. We quantify the damselfly wing reflectance from replicated sympatric and allopatric populations, and use receptor noise models to investigate the visual discriminability of the wing coloration for the bird, damselfly and fly vision systems, against natural backgrounds. We perform electroretinograms to study damselfly eye sensitivity. We also estimate damselfly predation risk in natural populations. We find that the chromatic component of wing coloration makes males highly discriminable to the predator, but not to the prey. However, female wing coloration is predominantly cryptic for the predator and prey, and interestingly, also for male damselflies. A female being cryptic to conspecifics likely reduces male harassment. The estimates of predation risk partially support the discriminability results. We also show that there is no difference in colour vision sensitivity between the two damselfly species and sexes, and no difference in wing coloration or its discriminability between sympatric and allopatric populations. Our results suggest that sexually selected traits can be antagonistically selected by predators and prey and that this antagonistic selection can be sex‐dependent: males are paying a large cost in terms of conspicuousness, while females remain mostly cryptic. Our study thus emphasizes the need for investigating visual communication at multitrophic levels since the degree of colour discriminability can differ between predators, prey and the focal species. Alay summary is available for this article. Abstract : Lay Summary